PENGELOLAAN LAPORAN KEUANGAN KERIPIK TEMPE DALAM MENGOPTIMALKAN PENDAPATAN - arlini, lidya; Hasan, M. Basri (Ekonomi Pembangunan Fakultas Ekonomi, 2024)
Managing finances is a reality that must be faced by every human being in everyday life, where one must manage finances properly in order to balance income and expenses, be able to meet life's needs and not get caught in financial difficulties. Therefore, financial intelligence is something that needs to be considered in a modern life like today. the case study in this research is krezi tempeh chips. In determining the selling price of Krezi Tempe Chips, careful calculations need to be made. This includes calculating the production cost per unit, adding the desired profit margin, considering market prices and demand, and taking into account factors such as consumer purchasing power and marketing strategies. With this approach, the selling price can be determined competitively and profitably for the business. Overall, good financial management and careful business analysis are key to the success of Krezi Tempe Chips. By integrating knowledge of financial management, business analysis, and marketing strategies, the business can grow and better compete in the market.